The Effect of Ballhandling Height Frequency Training and Barrier Training and Agility on the Ability to Lay -up Shoot Basketball - Anang Idris; Nasuka Nasuka; Taufiq Hidayah (STKIP Muhammadiyah Kuningan, 2023)
Purpose The purpose of this study was to determine the effect of ballhandling height frequency and barrier training on the ability to lay-up shoot basketball, to determine the effect of high and low agility on the results of lay-up shoot basketball, the interaction between ballhandling training methods and agility in extracurricular participants at SMK Negeri 1 Bengkulu Utara and North Bengkulu State Vocational School 2. This research method is experimental with a 2x2 design. The research sample was 21 athletes taken by total sampling technique. The instrument for measuring agility uses the zig-zag run test. The instrument measures lay-up shoot ability using a basketball lay-up shoot test. The data analysis technique was two-way ANOVA at a significant level of α=0.05. The results showed (1) there was a significant effect of high-frequency ballhandling and barrier training on the ability to lay up shoot basketball, (2) there was a significant difference in the results of significant high and low agility exercises on the ability to lay up shoot basketball. (3) There is no interaction between ballhandling and agility in determining the result of a basketball lay-up shoot. Then there is a significant influence between the influence of ballhandling exercises, height frequency and training obstacles and agility on the ability to lay up shoot basketball in extracurricular participants at SMK Negeri 1 Bengkulu Utara and SMK Negeri 2 Bengkulu Utara.